Desain Model Pembelajaran Reflective Moral Inquiry pada Pembelajaran PAI - Kasim Yahiji; Nur Ainiyah (Al-Ulum, 2019)
This article aims to explain the implementation of the model of reflective moral inquiry design in PAI learning. The reflective of the model of moral inquiry model design was developed based on reflective and self-analytical concepts with moral dilemmas approach that occur in daily life as a problem that must be solved by students through learning. This model is expected to make PAI learning more meaningful, students' knowledge about religious teachings can be a source of values ​​and driving behavior for students in real life. But in fact, the implementation of PAI learning is more dominant in initiating the achievement of the knowledge aspect because the teacher's mindset is still using teacher-centered in implementing learning.